PERAN MEDIA SOSIAL DALAM MENINGKATKAN PEMBELAJARAN BAHASA INGGRIS KALANGAN MAHASISWA: STUDI KUALITATIF PADA IAIN AMBON - Andi Masniati (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2024)
This study aims to examine the effect of the use of social media in English language learning among IAIN Ambon students. The study uses a qualitative approach with data collection techniques consisting of interviews and observations. The participants in this study were IAIN Ambon students who have utilized social media in their English language learning. The results of the study show that the use of social media can enhance students' English language skills. Students can improve their speaking, listening, reading, and writing skills by utilizing social media as a learning and practicing tool. The findings also indicate that the Input Hypothesis and Output Hypothesis theories can be applied in English language learning with social media. This suggests that the use of social media can be an effective alternative to enrich English language learning in higher education. Therefore, it is recommended that the use of social media in English language learning in higher education can be further developed and integrated into the learning curriculum.